2020
DOI: 10.1111/psyp.13662
|View full text |Cite
|
Sign up to set email alerts
|

Tears of joy, aesthetic chills and heartwarming feelings: Physiological correlates of Kama Muta

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 102 publications
(296 reference statements)
5
40
0
Order By: Relevance
“…Overall, the categorical objective occurrence of piloerection was quite low (3% in total across three videos; see S2 Table for complete frequencies). This is lower than, but similar to, recent reports (Zickfeld, Arriaga, Schubert, & Seibt, 2020). Surprisingly, 59% (across all three videos) selfreported experiencing goosebumps and 61% self-reported experiencing chills (counting those who answered above the lowest point on the scale).…”
Section: Frequency Of Piloerectionsupporting
confidence: 73%
“…Overall, the categorical objective occurrence of piloerection was quite low (3% in total across three videos; see S2 Table for complete frequencies). This is lower than, but similar to, recent reports (Zickfeld, Arriaga, Schubert, & Seibt, 2020). Surprisingly, 59% (across all three videos) selfreported experiencing goosebumps and 61% self-reported experiencing chills (counting those who answered above the lowest point on the scale).…”
Section: Frequency Of Piloerectionsupporting
confidence: 73%
“…For example, researchers have claimed they're related to being moved (Benedek & Kaernbach, 2011) or touched (Schubert, Zickfeld, Seibt, & Fiske, 2018). It's often believed they occur as a physiological correlate of awe (Quesnel & Riecke, 2018;Schurtz et al, 2012), although some evidence suggests otherwise (McPhetres & Shtulman, 2020;Zickfeld, Arriaga, Schubert, & Seibt, 2020). They are reported to occur at the peak of the pleasure response (e.e., the peak arousal hypothesis; Salimpoor, Benovoy, Longo, Cooperstock, & Zatorre, 2009) and in response to strong positive emotions (Grewe et al, 2011;Maruskin et al, 2012;Sumpf, Jentschke, & Koelsch, 2015;Wassiliwizky, Wagner, Jacobsen, & Menninghaus, 2015).…”
Section: Positive Emotionsmentioning
confidence: 99%
“…Researchers have recorded the occurrence of piloerection at several bodily locations. Most researchers (Benedek & Kaernbach, 2011;McPhetres & Shtulman, 2020;Quesnel & Riecke, 2018;Sumpf et al, 2015;Zickfeld et al, 2020) placed the camera on the non-dominant forearm or visually observed the arm (Craig, 2005). Wassiliwizky and colleagues Wassiliwizky, Koelsch, et al, 2017) placed the camera on the leg above the calf muscle.…”
Section: Goosecammentioning
confidence: 99%
“…This emotion is thought to be mixed in terms of valence (e.g., bittersweet), in that mostly positive but also negative feelings are elicited when feeling moved (Menninghaus et al, 2015;Vuoskoski & Eerola, 2017). Possibly as a reflection of this negative valence, some empirical evidence points to increased muscular activity around the eyes (e.g., corrugator) when people feel moved (Wassiliwizky et al, 2017a(Wassiliwizky et al, , 2017b; but see Zickfeld et al, 2020). Robust cross-cultural evidence also suggests that feeling moved is displayed and identified via tear droplets and crying (Schubert et al, 2018;Seibt et al, 2018;Zickfeld et al, 2019b).…”
Section: Nonverbal Expressions Of Positive Emotionsmentioning
confidence: 99%